An analytical study of some biomechanical variables related to rotation and their relationship to the achievement of 100m backstroke swimming for young people. - وليد عبد اللطيف; ساده محمد (Journal of Sport Science Technology and Physical Activities, 2025)
The research aims to "identify some of the biomechanical variables related to rotation to complete the 100m backstroke swimming for young people, as well as to identify the relationship between the biomechanical variables related to rotation and completing the 100m backstroke swimming for young people. To achieve the goal, the researchers used the descriptive approach in the style of correlational relationships to suit the problem and objectives of the research, The research sample was chosen intentionally, and they are swimmers from the national team in the 100m backstroke, numbering (4) for the youth group aged (15 - 17) years, which represents (80%) of the original research population, numbering (5) swimmers, One of the swimmers was excluded due to injury, and the researcher conducted the test and videotaping, after which the researcher conducted a movement analysis of the swimmers using the analysis program (kinovea) to extract the biomechanical variables related to rotation, Appropriate statistical treatments were carried out, and the researchers concluded that reaching an ideal propulsion position at the end of the rotation phase, especially in terms of the straightening of the torso and the body’s approach to the wall, is one of the fundamental factors that directly affects the amount of the resulting propulsion force. The more balanced and streamlined the body’s position during contact with the wall, the greater the value of the mechanical propulsion Which contributes to reducing the completion time and improving the overall performance of the swimmer in the following stages of the race. One of the major mistakes that some swimmers make is the increase in the push angle, which pushes the swimmer into the pool and takes him away from the straight path of the race, which makes him cover a greater distance and thus lose more time. The researchers recommend the need to work on correcting the propulsion position at the end of the turn, which will give the swimmer the ability to maintain body alignment with the water without deviation from the correct path, in addition to obtaining greater propulsion force, as well as conducting similar research on other types of swimming for the same distance